If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 = 4x + 20 Reorder the terms: 20 = 20 + 4x Add '-20' to each side of the equation. 20 + -20 = 20 + -20 + 4x Combine like terms: 20 + -20 = 0 0 = 20 + -20 + 4x Combine like terms: 20 + -20 = 0 0 = 0 + 4x 0 = 4x Solving 0 = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 0 + -4x = 4x + -4x Remove the zero: -4x = 4x + -4x Combine like terms: 4x + -4x = 0 -4x = 0 Divide each side by '-4'. x = 0 Simplifying x = 0
| 4/6-2=6 | | 8w+7=31 | | 11(z+2)-3(z-3)=4(2-3)+3(z-1) | | y=14-(5x-8) | | -19=-5x+12 | | -15=-4n+5 | | x^3+12x^2-3x-910=0 | | 10x-91=-107 | | 240-12x+x*x=0 | | 17x-(8x-4)=13 | | 5/6y=-20 | | -3x/8=-3 | | 2(5z+2)-6=88 | | (5x/8y^3)^2 | | x+24.8=48.5 | | 5(5x-1)=100 | | 40-2x=-38 | | 4x+9x-6x=42+7 | | 23=8x-9 | | 8-3n=n+4 | | -15x-60=-120 | | 10r+4=104 | | 0r+4=104 | | x+9=38 | | logx^2=8 | | -4y-6=1-3y | | -4x/5=60 | | -x+-x+-x+2=-x+-x+8 | | c+9=38 | | 3n-8=n+4 | | 19y-9=18y+27 | | 15=15x |